A high thermal conductivity carbon film with stable performance and resistance to frequent alternation of high and low temperatures and a preparation method thereof

By adopting a high thermal conductivity carbon film with a sandwich structure and combining magnetron sputtering technology, the problem of unstable structure and performance of the carbon film in an extremely temperature alternating environment is solved, and efficient performance stability of thermal management materials is achieved.

CN115786862BActive Publication Date: 2025-04-22ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211419749.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-14
Publication Date
2025-04-22
Estimated Expiration
2042-11-14

AI Technical Summary

Technical Problem

In extreme temperature alternating environments, carbon film materials exhibit structural and performance instability under low temperature impact, resulting in failure of thermal management materials.

Method used

A high thermal conductivity carbon film with a sandwich structure, including a base film, a metal-carbon amorphous transition layer and a metal plating layer, is prepared by magnetron sputtering technology to ensure the firm interface between the metal plating layer and the base carbon film to match the thermal expansion coefficient.

Benefits of technology

After frequent alternation of high and low temperatures, the carbon film maintains its original good morphology and excellent performance, has excellent temperature alternation resistance and performance stability, and the thermal conductivity retention rate is ≥90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115786862B_ABST
    Figure CN115786862B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of thermal management, and in particular to a high thermal conductivity carbon film with stable performance and resistance to frequent alternation of high and low temperatures and a preparation method thereof. The method forms a composite metal layer of a specific proportion on the surface of the high thermal conductivity carbon film by using magnetron sputtering coating technology. The dense metal coating repairs the macroscopic pore defects on the surface of the high thermal conductivity carbon film. At the same time, the flexible metal coating reduces the deformation ability of the carbon film surface, so that after repeated low-temperature shocks, the structural morphology and various performances can be maintained stable and excellent. The method combines the high thermal conductivity, high flexibility, and low density of the carbon film with the advantages of the magnetron sputtering process, such as mature equipment, simple operation, easy availability of raw materials, and large-scale production, to obtain a carbon-based thermal management material that can withstand low-temperature shocks in extreme environments and has stable performance. The thermally conductive film prepared by this method has broad application prospects in the fields of aerospace and nuclear reactor heat dissipation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of thermal management, and in particular to a high-temperature-resistant, high-thermal-conductivity carbon film with stable performance and a preparation method thereof. Background Art

[0002] In recent years, with the continuous development of information science and semiconductor technology, the demand for the integration of electronic devices has become increasingly higher, and various instruments and equipment are increasingly tending to be compact in structure and efficient in operation, which puts higher requirements on thermal management. High thermal conductivity materials are being used for thermal management of high-power electrical equipment in the military, automotive and aerospace fields. Carbon-based thin film materials have become an extremely attractive material due to their excellent thermal transport properties, outstanding thermal stability, inherent chemical resistance and excellent flexibility. Currently, the fastest-growing carbon-based thin film thermal management materials mainly include polyimide-based graphite films and graphene films.

[0003] As an emerging high-efficiency heat dissipation material, carbon-based thermal conductive film has been effectively applied in many fields at room temperature, such as high-power laser, semiconductor device packaging, MEMS, chip heat dissipation, etc. However, in addition to the need for thermal management at room temperature, effective heat dissipation is often required to ensure the effective operation and normal life of instruments and equipment under extreme conditions such as high and low temperature alternating environments, such as spacecraft thermal management and nuclear power plant reactor cooling and heat conduction devices. At present, spacecraft are mainly active in space near the earth, and the ambient temperature of this part of space can reach below -200℃. For spacecraft operating in space, due to the lack of air convection heat transfer, the sunny side absorbs the radiant heat of the sun, and the temperature can reach 100℃, while the side facing away from the sun is -100℃, which forms extremely high and low extreme temperature alternations. In nuclear power plants, in order to protect the fuel rods in the reactor and ensure that the reaction is controllable, the reactor must be temperature controlled. The cooling device is mainly a closed-loop liquid nitrogen (-196℃) cooling tower, and the heat dissipation material in it often needs to withstand frequent high and low temperature alternation processes.

[0004] However, in such an extreme temperature alternating environment, carbon films with thermal and chemical stability often show a lack of structural and performance stability under low temperature shock, resulting in their failure as thermal management materials. In the past, although there have been patents that use copper plating to solve similar problems, due to the poor wettability of metal copper and carbon-based materials, mismatched surface energy, mismatched thermal expansion coefficients, etc., the materials often show poor bonding between the coating and the substrate, and the coating metal is easy to peel off, making this method unable to achieve the expected effect. Summary of the invention

[0005] The purpose of the present invention is to improve the structural damage and performance loss of high thermal conductivity carbon film in a frequent temperature alternation environment, and to provide a high thermal conductivity carbon film with stable performance after low-temperature impact and a preparation method thereof.

[0006] The present invention adopts the following technical scheme: a high thermal conductivity carbon film with stable performance that can withstand frequent high and low temperature alternations, which not only has the advantages of high thermal conductivity, high flexibility, and low density, but also can maintain the original good morphology structure and various excellent properties after frequent high and low temperature alternations, and has excellent resistance to temperature alternation (-196°C to 25°C) and performance stability (thermal conductivity coefficient ≥1000W / m·K, thermal conductivity retention rate ≥90%). Specifically, the high thermal conductivity carbon film has a sandwich structure of a base film, a metal-carbon amorphous transition layer, and a metal coating. The strong interface bonding brought by the metal-carbon amorphous transition layer is conducive to achieving the structural stability of the high thermal conductivity composite material in an extreme temperature alternation environment. The base film has a thickness of 20 to 30 μm, the amorphous transition layer has a thickness of 5 to 10 nm, and the metal coating has a thickness of 1 to 2 μm. The metal coating reduces the deformation ability of the base carbon film surface, and the thermal expansion coefficients of the base carbon film and the coating metal match, so only small thermal stress is generated under frequent temperature changes, thereby maintaining a firm bond of the coating and good structural stability of the thermal conductive film under low-temperature impact.

[0007] The above-mentioned base film includes but is not limited to polyimide-based graphite film, graphene film, etc. The metal plating layer includes multiple metals, and at least one main metal with a mass content of more than 90%.

[0008] The present invention also provides a method for preparing a high thermal conductivity carbon film with stable performance that can withstand frequent alternations of high and low temperatures. The method comprises: using magnetron sputtering technology to plate a certain proportion of multiple high-purity metals on a base film to form a uniform and dense metal-plated thermal conductive carbon film; the multiple high-purity metals include a main metal with a mass content of more than 90%. In this method, the spontaneous wettability between the metal coating and the base carbon film is increased by alloying the coating metal, thereby increasing the interface bonding strength and forming an intermediate transition bonding layer, so that the dense metal coating protects the stability and excellence of its structural morphology and various performances after repeated low-temperature impacts. Specifically:

[0009] (1) The substrate film described above uses a highly graphitized (graphitization degree is above 90%) high thermal conductivity carbon material as the substrate film, so that only an extremely thin lattice defect layer appears during plasma pretreatment, ensuring that metal atoms cannot penetrate during magnetron sputtering, and only a transition interface layer is formed on the surface of the substrate carbon material at the micro-nano scale, thereby achieving the improvement of the interface bonding strength while ensuring that the overall high thermal conductivity of the composite material is not damaged.

[0010] (2) The multiple high-purity metals mentioned above refer to metals with a purity of more than 99%. The metal targets suitable for coating of the present invention include, but are not limited to, copper, silver, nickel, titanium, aluminum, cadmium and other metal elements that are easy to form carbides with the substrate material.

[0011] The present invention adopts a multi-metal element ratio in the selection of magnetron sputtering metal targets. The main metal content of the coating is greater than 90wt%, and the content of other added metals is controlled within 10wt%. For example, high-purity copper is used as the main metal, and a certain proportion of silver, nickel, titanium and other metals are also present in the surface coating. By alloying the coating metal, the spontaneous wettability between the metal coating and the base carbon film is increased, thereby increasing the interface bonding strength. The enhancement of interface bonding and the reduction of interface thermal resistance are achieved by regulating the coating phase composition.

[0012] Through the idea of ​​matrix alloying, a certain proportion is added to the magnetron sputtering target, and after the surface of the carbon material is metallized, an interfacial reaction occurs during the magnetron sputtering process to form a dense and uniform carbide transition layer. By regulating the ratio of various metals in the magnetron sputtering target, a transition intermediate layer of different thicknesses can be obtained, and the appropriate thickness of the intermediate layer can be adjusted to make it more compatible with the two-phase interface in terms of mechanical properties and thermophysical properties. For example, by designing the proportion of the metal components of the coating and regulating the transition bonding layer, the thermal expansion coefficients of the coating and the base film can be matched to achieve stable bonding of the coating under extreme and frequent temperature changes.

[0013] (3) Before magnetron sputtering, the base carbon film is plasma pretreated to slightly destroy the high crystallinity of the base carbon film and form an extremely thin amorphous layer, so that the subsequent sputtered metal coating and the base layer have a more solid bonding layer, so that the coating material and the surface of the base material can match each other, enhance the bonding force between the metal coating and the base carbon film, and increase the heat transport at the interface between the coating metal and the thermal conductive film. Specifically, oxygen plasma treatment is used on the surface of the high-crystalline base carbon material to oxidize its surface to form oxygen-containing functional groups, thereby improving the wettability between the carbon material and the coating metal. The carbon material substrate after plasma pretreatment can form a nano-covalent interface layer during magnetron sputtering. At the same time, by controlling the oxygen plasma treatment parameters, the crystallinity of the transition intermediate layer can be regulated, thereby matching the surface morphology of the base carbon film, such as surface roughness, surface micro-wrinkles, etc., thereby obtaining a more solid coating bond and reducing the phonon mismatch and scattering mismatch of carriers in the thermal conductivity of the composite material.

[0014] (4) According to the setting of sputtering parameters, the coating layer can be uniform and the thickness can be adjusted without affecting other properties of the base carbon film. At the same time, by setting the sputtering parameters, the thickness and crystallinity of the transition intermediate layer can be regulated to achieve the interface bonding and phonon coupling between the coating metal and the base carbon film. In addition, by setting the magnetron sputtering parameters, the size of the coating metal particles can be matched with the surface morphology of the thermal conductive film.

[0015] The beneficial effect of the present invention is that the method combines the high thermal conductivity, high flexibility and low density of the carbon film with the advantages of the magnetron sputtering process, which has mature equipment, simple operation, easy availability of raw materials and large-scale production, to obtain a carbon-based thermal management material that can withstand low-temperature impact of minus 196°C in extreme environments and has excellent performance.

[0016] The carbon-based thermally conductive film prepared by this method maintains good morphology and structure after repeated low-temperature impact. Compared with the original film whose thermal conductivity drops by 40%-50% after low-temperature impact, the thermal conductivity of the polyimide film prepared by this method remains almost unchanged within the acceptable error range of thermal conductivity measurement after the same number of impacts, showing good performance stability. At the same time, the carbon film prepared by this method also has good electrical conductivity, electromagnetic shielding performance and bending resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a schematic diagram of the preparation.

[0018] Figure 2 It is a schematic diagram of the metal-coated carbon film sandwich structure.

[0019] Figure 3 It is an optical image comparison of the surface morphology of the polyimide-based graphite film of Example 1 and Comparative Example 1 before and after 50 low-temperature impacts.

[0020] Figure 4 These are the relevant data of thermal conductivity, electrical conductivity, electromagnetic shielding performance, tensile strength and structural stability after the same number of low-temperature impacts of Example 1 and Comparative Example 1, where the unfilled area is Example 1 and the filled area is Comparative Example 1.

[0021] Figure 5 This is an optical image comparison of the surface morphology of a polyimide-based graphite film after 50 low-temperature impacts using copper, nickel, and titanium as metal coatings in Example 2.

[0022] Figure 6 This is an optical image comparison of the surface morphology of a polyimide-based graphite film after 50 low-temperature impacts using copper, silver, and titanium as metal coatings in Example 3.

[0023] Figure 7 Optical image comparison of the surface morphology of the graphene film of Example 4 and Comparative Example 4 before and after 50 low-temperature shocks.

[0024] Figure 8 The scanning electron microscope images of the surfaces of polyimide-based graphite films using a composite metal coating and a single metal coating are compared between Example 5 and Comparative Example 5. DETAILED DESCRIPTION

[0025] The present invention is specifically described below through examples. The examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art may make some non-essential changes and adjustments based on the contents of the above invention, which all fall within the scope of protection of the present invention.

[0026] Embodiment 1:

[0027] The polyimide-based graphite film with a graphitization degree of 90% was soaked in acetone for 0.5 hours before plasma treatment, washed with a large amount of distilled water, and placed in an oven for 24 hours to fully dry. A cold plasma reaction device was used, oxygen was used as the discharge gas, and the reaction conditions of power 80W and pressure 40Pa were used for 5 minutes to obtain the pretreated polyimide-based graphite film.

[0028] In the magnetron sputtering instrument, high-purity copper target (>99%) and nickel target (>99%) were used to control the ratio to obtain a composite metal target of Cu-1wt%Ni. The frequency of magnetron sputtering was 13000MHz and the output power was 3kW. Before the sputtering started, in order to reduce the contamination of gas impurities on the sample, the vacuum chamber was first evacuated to a vacuum degree of 5×10 -4 Pa, and then filled with high-purity argon (99.999%) as working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. Under the conditions of pressure 1.0Pa and power 20W for 60min, the sample of Example 1 is obtained, and its optical image is as follows Figure 3 As shown in a. Figure 2 It can be seen that the thickness of the amorphous transition layer is about 7nm. At the same time, the thickness of the carbon layer is about 21μm, and the thickness of the metal coating layer is 1μm.

[0029] Liquid nitrogen was used to simulate an extreme low temperature environment such as space. The sample was repeatedly immersed in liquid nitrogen and then taken out, and repeated 150 times. The results showed that its surface morphology did not change significantly. Its optical image is as follows Figure 3 As shown in b, it shows that it has good structural stability under low temperature impact.

[0030] Comparative Example 1:

[0031] Liquid nitrogen was used to simulate an extremely low temperature environment such as space, and an untreated polyimide-based thermal conductive film with a graphitization degree of 90% was directly placed on the surface of the film. The optical image is as follows: Figure 3 c, and then taken out after repeated immersion in liquid nitrogen. The results show that under the same number of low-temperature shocks as in Example 1, obvious bubbling occurs on the surface, and the morphology is severely damaged. The optical image is as follows Figure 3 As shown in d.

[0032] The thermal conductivity of the polyimide-based thermally conductive films obtained in Example 1 and Comparative Example 1 was tested using NETZSCH LFA 467.

[0033] Table 1: Thermal conductivity data of Example 1 and Comparative Example 1 after low temperature impact

[0034]

[0035] According to the data in Table 1, it can be seen that as the number of low-temperature impacts increases, the thermal conductivity of Example 1 remains almost unchanged, while the thermal conductivity of Comparative Example 1 decreases by nearly 50%, indicating that the polyimide-based thermally conductive film prepared by this method has good low-temperature impact performance stability.

[0036] By comparing Example 1 with Comparative Example 1, it can be seen that the polyimide thermal conductive film prepared by the method of the present invention has good structural stability and performance stability after low-temperature impact compared with the ordinary polyimide thermal conductive film. This is because the uniform and dense copper plating layer provides low-temperature impact protection for the polyimide film, and at the same time, the flexible copper plating layer of a certain thickness limits the surface deformation ability of the polyimide film after low-temperature impact, so that it has structural stability under low-temperature impact, and then maintains the stability of various performances including thermal conductivity.

[0037] Embodiment 2:

[0038] The polyimide-based graphite film with a graphitization degree of 90% was soaked in acetone for 0.5 hours before plasma treatment, washed with a large amount of distilled water, and placed in an oven for 24 hours to fully dry. A cold plasma reaction device was used, oxygen was used as the discharge gas, and the reaction conditions of power 80W and pressure 40Pa were used for 5 minutes to obtain the pretreated polyimide-based graphite film.

[0039] In the magnetron sputtering instrument, high-purity copper target (>99%), nickel target (>99%), and titanium target (>99%) were used to control the ratio to obtain a composite metal target of Cu-1wt%Ni-1wt%Ti. The frequency of magnetron sputtering was 13000MHz and the output power was 3kW. Before the sputtering started, in order to reduce the contamination of gas impurities on the sample, the vacuum chamber was first evacuated to a vacuum degree of 5×10 -4 Pa, and then filled with high-purity argon (99.999%) as working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. Under the conditions of pressure 1.0Pa and power 20W for 60min, the sample of Example 2 is obtained, and its optical image is as follows Figure 5 As shown in a, the thickness of the amorphous transition layer is about 10nm. At the same time, the thickness of the carbon layer is about 21μm, and the thickness of the metal coating layer is 1μm.

[0040] Liquid nitrogen was used to simulate an extreme low temperature environment such as space. The sample was repeatedly immersed in liquid nitrogen and then taken out, and repeated 150 times. The results showed that its surface morphology did not change significantly. Its optical image is as follows Figure 5 As shown in b, it shows that it has good structural stability under low temperature impact.

[0041] Embodiment 3:

[0042] The polyimide-based graphite film with a graphitization degree of 90% was soaked in acetone for 0.5 hours before plasma treatment, washed with a large amount of distilled water, and placed in an oven for 24 hours to fully dry. A cold plasma reaction device was used, oxygen was used as the discharge gas, and the reaction conditions of power 80W and pressure 40Pa were used for 5 minutes to obtain the pretreated polyimide-based graphite film.

[0043] In the magnetron sputtering instrument, high-purity copper target (>99%), silver target (>99%), and titanium target (>99%) were used to control the ratio to obtain a composite metal target of Cu-1wt%Ag-1wt%Ti. The frequency of magnetron sputtering was 13000MHz and the output power was 3kW. Before the sputtering started, in order to reduce the contamination of gas impurities on the sample, the vacuum chamber was first evacuated to a vacuum degree of 5×10 -4 Pa, and then filled with high-purity argon (99.999%) as working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. Under the conditions of pressure 1.0Pa and power 20W for 60min, the sample of Example 3 is obtained, and its optical image is as follows Figure 6 As shown in a, the thickness of the amorphous transition layer is about 8nm. At the same time, the thickness of the carbon layer is about 30μm, and the thickness of the metal coating layer is 2μm.

[0044] Liquid nitrogen was used to simulate an extreme low temperature environment such as space. The sample was repeatedly immersed in liquid nitrogen and then taken out, and repeated 150 times. The results showed that its surface morphology did not change significantly. Its optical image is as follows Figure 6 As shown in b, it shows that it has good structural stability under low temperature impact.

[0045] The thermal conductivity of the polyimide-based thermally conductive films obtained in Example 2 and Example 3 was tested using NETZSCH LFA 467.

[0046] Table 2: Thermal conductivity data table of Example 2 and Example 3 after low temperature impact

[0047]

[0048] According to the data in Table 2, it can be seen that the polyimide-based thermally conductive film with different metal types and ratios of surface coatings has very little loss in thermal conductivity as the number of low-temperature impacts increases, indicating that the polyimide thermally conductive film prepared by this method has good low-temperature impact performance stability.

[0049] Embodiment 4:

[0050] The graphene film with a graphitization degree of 95% was soaked in acetone for 0.5 hours before plasma treatment, washed with a large amount of distilled water, and placed in an oven for 24 hours to fully dry. A cold plasma reaction device was used, oxygen was used as the discharge gas, and the reaction conditions of power 80W and pressure 40Pa were used for 5 minutes to obtain the pre-treated graphene film.

[0051] In the magnetron sputtering instrument, high-purity copper target (>99%) and nickel target (>99%) were used to control the ratio to obtain a composite metal target of Cu-1wt%Ni. The frequency of magnetron sputtering was 13000MHz and the output power was 3kW. Before the sputtering started, in order to reduce the contamination of gas impurities on the sample, the vacuum chamber was first evacuated to a vacuum degree of 5×10 -4 Pa, and then filled with high-purity argon (99.999%) as working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. Under the conditions of pressure 1.0Pa and power 20W for 60min, the sample of Example 4 is obtained, and its optical image is as follows Figure 7 As shown in a, the thickness of the amorphous transition layer is about 6nm. At the same time, the thickness of the carbon layer is about 21μm, and the thickness of the metal coating layer is 1μm.

[0052] Liquid nitrogen was used to simulate an extreme low temperature environment such as space. The sample was repeatedly immersed in liquid nitrogen and then taken out, and repeated 150 times. The results showed that its surface morphology did not change significantly. Its optical image is as follows Figure 7 As shown in b, it shows that it has good structural stability under low temperature impact.

[0053] Comparative Example 4:

[0054] Liquid nitrogen was used to simulate an extremely low temperature environment such as space, and the untreated graphene film was directly placed on the surface of the graphene film. The optical image is as follows: Figure 7 c, and then taken out after repeated immersion in liquid nitrogen. The results show that under the same number of low-temperature shocks as in Example 4, obvious bubbling occurs on the surface, and the morphology is severely damaged. The optical image is as follows Figure 7 As shown in d.

[0055] The thermal conductivity of the polyimide-based thermally conductive films obtained in Example 4 and Comparative Example 4 was tested using NETZSCH LFA 467.

[0056] Table 3: Thermal conductivity data of Example 4 and Comparative Example 4 after low temperature impact

[0057]

[0058]

[0059] According to the data in Table 3, it can be seen that as the number of low-temperature impacts increases, the thermal conductivity of Example 4 remains almost unchanged, while the thermal conductivity of Comparative Example 4 decreases by nearly 40%, indicating that the graphene thermal conductive film prepared by this method has good low-temperature impact performance stability.

[0060] By comparing Example 4 with Comparative Example 4, it can be seen that the graphene film prepared by the method of the present invention has good structural stability and performance stability after low-temperature impact compared with the ordinary graphene film. This is because the uniform and dense copper plating layer provides low-temperature impact protection for the graphene film. At the same time, the flexible copper plating layer of a certain thickness limits the surface deformation ability of the graphene film after low-temperature impact, so that it has structural stability under low-temperature impact, and then maintains the stability of various performances including thermal conductivity.

[0061] Embodiment 5:

[0062] The polyimide-based graphite film with a graphitization degree of 90% was soaked in acetone for 0.5 hours before plasma treatment, washed with a large amount of distilled water, and placed in an oven for 24 hours to fully dry. A cold plasma reaction device was used, oxygen was used as the discharge gas, and the reaction conditions of power 80W and pressure 40Pa were used for 5 minutes to obtain the pretreated polyimide-based graphite film.

[0063] In the magnetron sputtering instrument, high-purity copper target (>99%), nickel target (>99%) and titanium target (>99%) were used to control the ratio to obtain a composite metal target of Cu-1wt%Ni-1wt%Ti. The frequency of magnetron sputtering was 13000MHz and the output power was 3kW. Before the sputtering started, in order to reduce the contamination of gas impurities on the sample, the vacuum chamber was first evacuated to a vacuum degree of 5×10 -4 Pa, and then filled with high-purity argon (99.999%) as working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. Under the conditions of pressure 1.0Pa and power 20W for 60min, the sample of Example 5 is obtained, and its SEM image is as follows Figure 8 As shown in a, the thickness of the amorphous transition layer is about 5nm. At the same time, the thickness of the carbon layer is about 21μm, and the thickness of the metal coating layer is 1μm.

[0064] Comparative Example 5:

[0065] The polyimide-based graphite film with a graphitization degree of 90% was soaked in acetone for 0.5 hours before plasma treatment, washed with a large amount of distilled water, and placed in an oven for 24 hours to fully dry. A cold plasma reaction device was used, oxygen was used as the discharge gas, and the reaction conditions of power 80W and pressure 40Pa were used for 5 minutes to obtain the pretreated polyimide-based graphite film.

[0066] Only high-purity copper targets were used in the magnetron sputtering instrument. The frequency of magnetron sputtering was 13000MHz and the output power was 3kW. Before the sputtering started, the vacuum chamber was evacuated to a vacuum degree of 5×10 -4 Pa, and then filled with high-purity argon (99.999%) as the working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. Under the conditions of pressure 1.0Pa and power 20W for 60min, the SEM image is as follows Figure 8 As shown in b, the carbon layer is about 21 μm thick, the metal coating is 1 μm thick, and there is no transition layer.

[0067] By comparing Example 5 with Comparative Example 5, it can be seen that the polyimide thermal conductive film prepared by the method of the present invention using the composite metal coating has good interface bonding and coating firmness compared with the ordinary single metal coating polyimide thermal conductive film, so that the surface of the thermal conductive film has a more uniform and dense metal coating.

[0068] Table 4: Thermal conductivity data of Example 5 and Comparative Example 5 after low temperature impact

[0069]

[0070] Embodiment 6:

[0071] The highly graphitized (95%) graphene film after heat treatment at 3000℃ was soaked in acetone for 0.5h before plasma treatment, washed with a large amount of distilled water, and placed in an oven for 24h to fully dry. A cold plasma reaction device was used, oxygen was used as the discharge gas, and the reaction conditions of power 80W and pressure 40Pa were used for 5min to obtain the pre-treated graphene film.

[0072] In the magnetron sputtering instrument, high-purity copper target (>99%) and titanium target (>99%) were used to control the ratio to obtain a composite metal target of Cu-1wt%Ti. The frequency of magnetron sputtering was 13000MHz and the output power was 3kW. Before the sputtering started, in order to reduce the contamination of gas impurities on the sample, the vacuum chamber was first evacuated to a vacuum degree of 5×10 -4Pa, and then filled with high-purity argon (99.999%) as working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. Under the conditions of pressure 1.0Pa and power 20W for 60min, the sample of Example 6 is obtained. The thickness of its amorphous transition layer is about 6nm. At the same time, the thickness of the carbon layer is about 21μm, and the thickness of the metal coating layer is 1μm.

[0073] Liquid nitrogen was used to simulate an extreme low temperature environment such as space. The samples obtained above were repeatedly immersed in liquid nitrogen and then taken out, and this cycle was repeated 150 times to measure their thermal conductivity.

[0074] Comparative Example 6:

[0075] The partially graphitized (75%) graphene film after heat treatment at 1200°C was soaked in acetone for 0.5h before plasma treatment, washed with a large amount of distilled water, and placed in an oven for 24h to fully dry. A cold plasma reaction device was used, oxygen was used as the discharge gas, and the reaction conditions of power 80W and pressure 40Pa were used for 5min to obtain the pretreated graphene film.

[0076] In the magnetron sputtering instrument, high-purity copper target (>99%) and titanium target (>99%) were used to control the ratio to obtain a composite metal target of Cu-1wt%Ti. The frequency of magnetron sputtering was 13000MHz and the output power was 3kW. Before the sputtering started, in order to reduce the contamination of gas impurities on the sample, the vacuum chamber was first evacuated to a vacuum degree of 5×10 -4 Pa, and then filled with high-purity argon (99.999%) as the working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. The treatment is carried out for 60min under the conditions of pressure 1.0Pa and power 20W. The thickness of its amorphous transition layer is about 30nm. At the same time, the thickness of the carbon layer is about 21μm, and the thickness of the metal coating is 1μm.

[0077] Liquid nitrogen was used to simulate an extreme low temperature environment such as space. The samples obtained above were repeatedly immersed in liquid nitrogen and then taken out, and this cycle was repeated 150 times to measure their thermal conductivity.

[0078] Table 5: Thermal conductivity data of Example 6 and Comparative Example 6 after low temperature impact

[0079]

[0080] By comparing Example 6 with Comparative Example 6, it can be seen that the graphene composite film prepared by the method described in the present invention has better thermal conductivity and good performance stability after low-temperature impact than the ordinary composite graphene film. This is because the highly crystallized substrate has good electrical conductivity so that the heat transfer carriers have more transport channels. At the same time, the highly crystallized structure avoids the large-scale generation of defects in subsequent processing. The uniform and dense metal coating thus obtained provides low-temperature impact protection for the graphene film. At the same time, the flexible coating with a certain thickness and a firm bond limits the deformation ability of the surface of the graphene film after low-temperature impact, so that it has structural stability under low-temperature impact, thereby maintaining the stability of various aspects of performance including thermal conductivity.

[0081] Embodiment 7:

[0082] The polyimide-based graphite film with a graphitization degree of 90% was soaked in acetone for 0.5 hours before plasma treatment, washed with a large amount of distilled water, and placed in an oven for 24 hours to fully dry. A cold plasma reaction device was used, oxygen was used as the discharge gas, and the reaction conditions of power 80W and pressure 40Pa were used for 5 minutes to obtain the pretreated polyimide-based graphite film.

[0083] In the magnetron sputtering instrument, high-purity copper target (>99%) and nickel target (>99%) were used to control the ratio to obtain a composite metal target of Cu-1wt%Ni. The frequency of magnetron sputtering was 13000MHz and the output power was 3kW. Before the sputtering started, in order to reduce the contamination of gas impurities on the sample, the vacuum chamber was first evacuated to a vacuum degree of 5×10 -4 Pa, and then filled with high-purity argon (99.999%) as working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. Under the conditions of pressure 1.0Pa and power 20W, the sample of Example 7 is obtained. The thickness of its amorphous transition layer is about 7nm. At the same time, the thickness of the carbon layer is about 21μm, and the thickness of the metal coating layer is 1μm.

[0084] Liquid nitrogen was used to simulate an extreme low temperature environment such as space. The samples obtained above were repeatedly immersed in liquid nitrogen and then taken out, and this cycle was repeated 150 times to measure their thermal conductivity.

[0085] Comparative Example 7:

[0086] The polyimide-based graphite film with a graphitization degree of 90% was directly treated with a high-purity copper target (>99%) and a nickel target (>99%) to obtain a Cu-1wt%Ni composite metal target with a controlled ratio. The surface was coated in a magnetron sputtering apparatus with a frequency of 13000MHz and an output power of 3kW. Before the sputtering started, the vacuum chamber was first evacuated to a vacuum degree of 5×10 -4 Pa, and then filled with high-purity argon (99.999%) as the working gas, the argon flow rate is 20sccm, and the temperature of the sputtering substrate is room temperature. During the working process, the sample holder rotates at a speed of 20r / min to reduce the self-shadow effect of copper ions due to the incident direction. The treatment is carried out for 60 minutes under the conditions of pressure 1.0Pa and power 20W. The thickness of its amorphous transition layer is about 3nm. At the same time, the thickness of the carbon layer is about 21μm, and the thickness of the metal coating is 1μm.

[0087] Liquid nitrogen was used to simulate an extreme low temperature environment such as space. The samples obtained above were repeatedly immersed in liquid nitrogen and then taken out, and this cycle was repeated 150 times to measure their thermal conductivity.

[0088] Table 6: Thermal conductivity data of Example 7 and Comparative Example 7 after low temperature impact

[0089]

[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a high thermal conductivity carbon film with stable performance and high resistance to frequent high and low temperature changes, characterized in that: The method comprises: using magnetron sputtering technology to plate a certain proportion of multiple high-purity metals on a base carbon film to form a uniform and dense metal-plated thermally conductive carbon film; the multiple high-purity metals include a main metal with a mass content of more than 90%; The graphitization degree of the base carbon film is above 90%. Before magnetron sputtering, the base carbon film is subjected to plasma pretreatment. The main metal is copper, and the other metals are at least one or more of nickel, titanium, aluminum, and cadmium.

2. The high thermal conductivity carbon film with stable performance and high resistance to frequent alternation of high and low temperatures prepared by the method of claim 1 is characterized in that: It has a sandwich structure of a base carbon film, a metal-carbon amorphous transition layer and a metal coating, wherein the base carbon film is 20-30 μm thick, the metal-carbon amorphous transition layer is 5-10 nm thick, and the metal coating is 1-2 μm thick.

3. The high thermal conductivity carbon film with stable performance and high resistance to frequent high and low temperature changes according to claim 2, characterized in that: The base carbon film is a polyimide-based graphite film or a graphene film.

Citation Information

Patent Citations

  • High heat conductivity type graphite film-metal composite material and preparation method thereof

    CN109234691A

  • High-thermal-conductivity composite graphite cooling fin and preparation method thereof

    CN110744875A